Designing Hybrid Human-Machine Workplaces - Gajšek, Brigita (Strenghtening Supply Chains: Strategies for Resilience and Agility, 2026)
During the transition to Industry 4.0, workplaces are being transformed from manual through human-machine hybrids to automated, autonomous and smart ones. Each of the aforementioned designs represents a development challenge. A particular challenge is the development of hybrid workplaces, where using the potential of man and machine to the maximum extent possible is necessary. Lean principles are followed in designing workplaces and processes, reflected in the efficient use of time and minimized losses, as well as ergonomics principles. Due to the lack of labor force and the aging of the population, concern for maintaining employees' health is an important guideline for designing workplaces for the future. Knowing the basics of lean, time management and ergonomics while simultaneously learning about the computer environment for designing workplaces can be a good starting point for the prudent designing of the renovation of traditional workplaces into Industry 4.0 workplaces.